An Integrated Environmental Assessment of MSW Management in a Large City of a Developing Country: Taking the First Steps Towards a Circular Economy Model - Lara-Topete, Gary Ossmar; Yebra-Montes, Carlos; Orozco-Nunnelly, Danielle A.; Robles-Rodríguez, Carlos Eduardo; Gradilla-Hernández, Misael Sebastián (Frontiers in Environmental Science, 2022)
Most of the municipal solid waste (MSW) in developing countries ends up in landfills. For example, more than 95% of the MSW generated in Latin America is disposed of in some type of landfill. Factors such as high organic compositions, low recycling rates and poor control over the disposal sites greatly increase the environmental impacts associated with MSW management in this region, resulting in increased emissions of greenhouse gases (GHGs) and runoff of leachates. Therefore, local governments in Latin America are making efforts to transition to more “circular” management models for MSW. This is the case in the Guadalajara Metropolitan Area (GMA), the third most populous city in Mexico, where the implementation of the following two mechanical biological treatment (MBT) alternatives are being considered: 1) a high-capacity mechanical sorting facility with no biological treatment and 2) a medium-capacity mechanical sorting facility coupled with a composting process. Thus, the aim of the present study was to assess the environmental performance of the current MSW management system (baseline) as compared to the two potential MBT alternatives through life cycle assessment (LCA) and sensitivity analyses. Furthermore, by using a SWOT analysis, this study aimed to provide insights into the main economical, sociocultural, legal, political and technological/infrastructure challenges that need to be overcome in the GMA, as well as other cities in developing countries, in order to transition to circular MSW management models. An assessment of global warming potential (measured in Gg CO2-eq/year) indicated that the current MSW management system (baseline) results in the emission of 111.21 Gg CO2-eq/year, while the two potential alternative scenarios displayed a net emissions reduction of 24 and 34%, respectively, due to material recycling and the substitution of petroleum coke with refuse-derived fuel (RDF) in cement kilns. When evaluating abiotic resource depletion (measured in Gg Sb-eq/year), the potential alternative scenarios both outperformed the baseline with savings increases between 3,380 and 3,501%. This result is largely attributed to the decrease in fossil fuel consumption (due to the substitution of petroleum coke with RDF), which provides a potential reduction of 5.62 Gg Sb-eq/year. The sensitivity analysis revealed that several key parameters, such as the fraction of food and plastic wastes in the MSW, can alter the scenario rankings. Recycling of the recovered materials and treatment of the organic fraction were found to be key strategies for a reduction in direct environmental impacts. Additionally, better management of waste picker activities, standardization of landfill operations and enhancement of material separation and selective collection must be addressed prior to the introduction of new treatment technologies. The results of the study herein can assist in the formation of policies to improve the feasibility of MBT implementation and drive the first steps towards a circular economy model in the GMA, as well as other cities within Latin American and Caribbean regions with similar characteristics.